1998
DOI: 10.1007/s002329900410
|View full text |Cite
|
Sign up to set email alerts
|

Voltage-independent Adaptation of Mechanosensitive Channels in Escherichia coli Protoplasts

Abstract: Mechanosensitive (MS) ion channels, with 560 pS conductance, opened transiently by rapid application of suction pulses to patches of E. coli protoplast membrane. The adaptation phase of the response was voltage-independent. Application of strong suction pulses, which were sufficient to cause saturation of the MS current, did not abolish the adaptation. Multiple-pulse experimental protocols revealed that once MS channels had fully adapted, they could be reactivated by a second suction pulse of similar amplitude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 18 publications
2
52
0
Order By: Relevance
“…This suggests that the decline of activities was due to the lack of recovery of the adapted channels from their inactive state. We found previously that the recovery rate from an inactive state of the YggB channels was 72 and 95% following intervals of 60 and 120 s, respectively (18). In the experiment presented in Fig.…”
Section: Nisupporting
confidence: 51%
See 4 more Smart Citations
“…This suggests that the decline of activities was due to the lack of recovery of the adapted channels from their inactive state. We found previously that the recovery rate from an inactive state of the YggB channels was 72 and 95% following intervals of 60 and 120 s, respectively (18). In the experiment presented in Fig.…”
Section: Nisupporting
confidence: 51%
“…Even small changes in the position of the ␤-barrel strands may affect Ni 2ϩ binding to the histidine tags. We demonstrated previously that exposure of the cytoplasmic side of the MscS channels to 1 mg/ml Pronase almost entirely abolished their activities (18). We concluded that Pronase removed responsiveness of the channels to the membrane tension by disrupting the tension transmission mechanism responsible for the opening of the channel.…”
Section: Discussionmentioning
confidence: 68%
See 3 more Smart Citations